Nutrient contributions from septic systems in nutrient-sensitive watersheds: Quantifying nutrient inputs, reduction methods, and economic feasibility - Iverson, Guy (East Carolina University, 2019)
Eutrophication of surface waters is a global issue threatening aquatic ecosystems and recreational opportunities. Nutrient management strategies exist to reduce nutrient inputs from various sources; however, septic systems are typically not listed in these strategies. The goal of this research was to: 1) quantify mass export of nitrogen and phosphorus from septic-dominated watersheds relative to control watersheds (those without significant septic system usage); 2) implement retrofit best management practices (BMPs) in septic-dominated watersheds to quantify nutrient mass attenuation; and 3) perform cost-benefit analysis (CBA) to compare economic feasibility of using retrofit BMPs to conversion of septic to sewer. Results showed that nutrient exports were significantly elevated from watersheds with a high-density (HD) of septic systems (approximately 1.8 systems ha-1). Mass exports of total dissolved nitrogen (TDN) and phosphate from HD watersheds (median: 4.9 kg-N yr-1 ha-1; 0.2 kg-P yr-1 ha-1) were approximately 5 and 10 times greater, respectively, than control watershed and low-density septic watersheds. An in-stream bioreactor (IBR) was installed upstream from a natural wetland (NW) to improve watershed attenuation of nutrients. Mass inputs of TDN and phosphate to the IBR were approximately 177.1 g-N day-1 (14.8 g-N day-1 ha-1) and 24.6 g-P day-1 (2.1 g-P day-1 ha-1), respectively. Mass exports of TDN and phosphate from the NW were 31.9 g-N day-1 (0.3 g-N day-1 ha-1) and 2.1 g-P day-1 (0.02 g-P day-1 ha-1), respectively, which was a load reduction of 82% (98% area normalized) and 91% (99% area normalized) for TDN and phosphate, respectively. CBAs implied that constructing and maintaining septic systems along with an IBR and NW was economically feasible based on nutrient attenuation benefits alone. Costs associated with converting from septic to municipal sewer along with utility fees outweighed potential nutrient removal benefits. This research suggests that including septic systems among nutrient management strategies may help North Carolina and other regions achieve nutrient reduction goals.
Keywords: nutrient; septic; bmp; economic; bioreactor; wetland; Nutrient pollution of water; Watersheds; Sewage; Water quality management